2023
DOI: 10.3389/fphar.2023.1146468
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-related molecular subtypes direct T cell exhaustion phenotypes and therapeutic strategies for patients with lung adenocarcinoma

Abstract: Background: T cell exhaustion (TEX) heterogeneity leads to unfavorable immunotherapeutic responses in patients with cancer. Classification of TEX molecular phenotypes is pivotal to overcoming TEX and improving immunotherapies in the clinical setting. Cuproptosis is a novel form of programmed cell death associated with tumor progression. However, the relation between cuproptosis-related genes (CuRGs) and the different TEX phenotypes has not been investigated in lung adenocarcinoma (LUAD).Methods: Unsupervised h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…TEX-related genes can be extracted from CD8TEX cells from the scRNA-seq database. Additionally, TEX-based gene signatures have been widely used to predict prognostic, molecular, and immune features, as well as therapeutic responses in several tumors, including LIHC, lung adenocarcinoma, and NSCLC [ 34 , 35 , 36 , 37 ]. In this study, we identified and validated a TEX-related signature for predicting the prognosis and immune response in PACA using integrated analysis of scRNA-seq and bulk RNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…TEX-related genes can be extracted from CD8TEX cells from the scRNA-seq database. Additionally, TEX-based gene signatures have been widely used to predict prognostic, molecular, and immune features, as well as therapeutic responses in several tumors, including LIHC, lung adenocarcinoma, and NSCLC [ 34 , 35 , 36 , 37 ]. In this study, we identified and validated a TEX-related signature for predicting the prognosis and immune response in PACA using integrated analysis of scRNA-seq and bulk RNA sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“… 86 In addition, cuproptosis‐related genes (CRGs) may influence T cell exhaustion phenotype and serve as effective prognostic indicators for lung adenocarcinoma. 87 In Temporal lobe epilepsy, upregulated CRGs may promote peripheral CD4 + and CD8 + T cell infiltration into epileptic focus, which increases seizure frequency. 88 In patients with pancreatic adenocarcinoma, CRGs may drive the infiltration of antitumor components, such as activated CD4 + and CD8 + T cells, which are associated with longer survival.…”
Section: The Role Of Essential Trace Elementsmentioning
confidence: 99%